Tracing Metafictional Phenomena in Contemporary German Literature (KULT_online, 2011)
The anthology Metafiktion. Analysen zur deutschsprachigen Gegenwartsliteratur (Metafiction. Interpretations of contemporary German literature) examines different forms of metafiction in German literature from 1990 to today. The essays, which deal with a broad spectrum of both well- and lesser-known authors, are a welcome addition to a barely explored research area. Moreover, the contributors are concerned with offering new perspectives on the texts by using concepts and theories of metafictional scholarship. Less satisfactory is the irregular quality of the anthology, and that it offers neither a contextualizing introduction nor a clearly defined structure. This is why it does not meet the criteria for a systematic study, but is rather an accumulation of single observations.